1977
DOI: 10.1042/bj1670847
|View full text |Cite
|
Sign up to set email alerts
|

Rate-limiting steps in the cytidine pathway for the synthesis of phosphatidylcholine and phosphatidylethanolamine

Abstract: An analysis of the available data on the cytidine pathway for the synthesis of phosphatidylcholine and phosphatidylethanolamine, by the logic derived from the theoretical principles of metabolic regulation, shows that the first two reactions catalysed by choline (ethanolamine) kinase and phosphocholine (phosphoethanolamine) cytidylyltransferase are rate-limiting, whereas the phosphocholine (phosphoethanolamine) transferase step is near equilibrium in rat liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…The exact biochemical mechanism explaining the changes in concentration of PEt is not well described in the literature. Experimental data suggest that the cytidyltransferase reaction is the rate limiting step [21] in the enzymatic reactions involved in the de novo synthesis of phosphatidylethanolamine, although the ethanolamine-kinase is also in disequilibrium [22]. Consequently, an increase in the rate of the cytidyltransferase reaction should lead to a decrease of PEt and an increase in phosphatidylethanolamine.…”
Section: Resultsmentioning
confidence: 99%
“…The exact biochemical mechanism explaining the changes in concentration of PEt is not well described in the literature. Experimental data suggest that the cytidyltransferase reaction is the rate limiting step [21] in the enzymatic reactions involved in the de novo synthesis of phosphatidylethanolamine, although the ethanolamine-kinase is also in disequilibrium [22]. Consequently, an increase in the rate of the cytidyltransferase reaction should lead to a decrease of PEt and an increase in phosphatidylethanolamine.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of theoretical principles of metabolic regulation, Infante recently concluded that cholineand ethanolaminephosphotransferase are not rate-limiting enzymes in the synthesis of PC and PE (46). From the data presented in Table III a role of these enzymes in the regulation of PC and PE synthesis can, nevertheless, not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Activities of the phosphoryltransferases and cytidylyltransferases, which are the only ratelimitmg steps of the cytidine pathway for PC and PE synthesis [ 15,16,24,25], showed neghgrble activities in the gastrocnemius of C57BL/6J mice. Activities of choline kinase, P-cholme cytidylyltransferase and that of the ethanolamine analogs showed rates of less than 0.004 nmol/mg protein per min (not shown).…”
Section: Resultsmentioning
confidence: 99%